A Mixed-Method Approach to Explore Successful Recruitment and Treatment of Minority Patients on Therapeutic Cancer Clinical Trials at a Tertiary Referral Center Using Photo-Elicitation Interviews - Katharine A.R. Price; Rahma Warsame; Mary O'Shea; Yonghun Kim; Sara A. Ellingson; Gladys B. Asiedu (Mary Ann Liebert, 2024)
Introduction: Under-represented minority patients (URM) enroll in cancer clinical trials (CCT) at low rates. To gain insight into barriers and facilitators to CCT enrollment, we conducted a mixed method study of URM patients who were successfully treated on a therapeutic CCT from 2018?2021 at all institutional sites. Methods: A retrospective chart review of 270 minority patients was conducted to identify patient demographics and characteristics. All living URM patients were requested to participate in a survey and qualitative interview using a photo elicitation technique. Results: Most patients who participated in a CCT were patients with solid tumors, metastatic disease, and did not live in a rural area. Survey data showed that the two most significant drivers of CCT enrollment were potential of benefit to self and to others (altruism). Direct recommendation from a healthcare provider to participate in CCT was critical. URM patients enrolled on a CCT experience a significant burden of symptoms and financial distress. Key themes identified from the interviews that motivated patients to participate included chance for cure, staying positive, altruism and advancement of science, and having diverse representation in research. Patient-level facilitators to participation included social support, cost coverage, and limited treatment options. Sytematic facilitators identified included minimizing logistical barriers, decentralizing cancer clinical trials, increasing awareness via patient narratives, diversifying research staff, minimizing cost, and being clear on puropose and benefit of the trial. Conclusion: Success stories of minority recruitment can provide useful information to enhance minority accrual. Photo elicitation interviews provide rich narratives of patient experience.